2022
DOI: 10.3389/fonc.2022.1031944
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA damage response as a potential therapeutic strategy for head and neck squamous cell carcinoma

Abstract: Cells experience both endogenous and exogenous DNA damage daily. To maintain genome integrity and suppress tumorigenesis, individuals have evolutionarily acquired a series of repair functions, termed DNA damage response (DDR), to repair DNA damage and ensure the accurate transmission of genetic information. Defects in DNA damage repair pathways may lead to various diseases, including tumors. Accumulating evidence suggests that alterations in DDR-related genes, such as somatic or germline mutations, single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 147 publications
0
5
0
Order By: Relevance
“…Given that IR, including X-ray radiation and PBT, cause the therapeutic effect through targeting and damaging the DNA particularly through the formation of potentially toxic DSBs, a logical approach is to combine inhibitors of key proteins involved in the cellular DDR to potentiate the effects of IR on tumour models. The protein kinases ATM, ATR and DNA-Pkcs are well characterised enzymes involved in the signalling and repair of DSBs, and therefore there have been some studies that have explored the effect of inhibiting these kinases in radiosensitising HNSCC [ 14 16 ]. These studies have revealed an important potential for inhibiting ATM, ATR and DNA-Pkcs in enhancing the sensitivity of HNSCC to X-ray irradiation, but which are difficult to compare due to the different inhibitors used and their ranging potency and selectivity, as well as the various cell models employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that IR, including X-ray radiation and PBT, cause the therapeutic effect through targeting and damaging the DNA particularly through the formation of potentially toxic DSBs, a logical approach is to combine inhibitors of key proteins involved in the cellular DDR to potentiate the effects of IR on tumour models. The protein kinases ATM, ATR and DNA-Pkcs are well characterised enzymes involved in the signalling and repair of DSBs, and therefore there have been some studies that have explored the effect of inhibiting these kinases in radiosensitising HNSCC [ 14 16 ]. These studies have revealed an important potential for inhibiting ATM, ATR and DNA-Pkcs in enhancing the sensitivity of HNSCC to X-ray irradiation, but which are difficult to compare due to the different inhibitors used and their ranging potency and selectivity, as well as the various cell models employed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their paramount importance in resolving DNA DSB damage, ATM, ATR and DNA-Pkcs have been increasingly investigated to confirm whether their inhibition could improve the impact of X-ray irradiation in decreasing HNSCC cell survival [ 14 16 ]. Using HNSCC cell lines (HN4 and HN5), treatment with the DNA-Pkcs inhibitor KU-0060648 increased cellular radiosensitivity associated with increased radiation-induced RAD51 and γH2AX foci, along with G2/M cell cycle arrest [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…PARP1/2 inhibitors are shown to be a better approach to target specific DDR in cancer, with good clinical response in many solid tumors, including HNSCC 111–113 . Nowadays, there are some PARP1/2 inhibitors approved by the FDA for clinical use, such as Olaparib, whose combination with other anticancer therapies for HNSCC is under investigation and shows promising results 114 …”
Section: Discussionmentioning
confidence: 99%
“…[111][112][113] Nowadays, there are some PARP1/2 inhibitors approved by the FDA for clinical use, such as Olaparib, whose combination with other anticancer therapies for HNSCC is under investigation and shows promising results. 114 Despite the strong association of KMT2C/D members with the regulation of different pathways that could lead to tumor progression, disease aggressiveness, and DNA damage accumulation, besides its potential as a biomarker to predict immunotherapy response, further studies are needed to better clarify such mechanisms due to the heterogeneity found in this systematic review for both genes.…”
Section: Genetic Alterationsmentioning
confidence: 91%
“…Genetic abnormalities associated with the repair of DSBs in HNSCC have been reviewed recently [57]. Whilst abnormalities in NHEJ and HR/FA genes have been described in both OSCC [47,[66][67][68][69][70] and HNSCC [59,71,72], the overall picture remains unclear.…”
Section: Repairmentioning
confidence: 99%